Diagnosis and conservative management of late tracheotomy complications in chronic ventilator‐dependent patients. Issue 5 (12th July 2014) - Ilan, Ophir; Gross, Menachem; Zaltzman, Yacov; Sasson, Ady; Marcus, Esther‐Lee
Abstract: Background: Complications associated with long‐term tracheotomy are obstruction of the distal end of the tube by granulation tissue and tracheomalacia. These complications have traditionally been surgically treated. Methods: Prospective study in a chronic ventilator‐dependent division, including 234 consecutive patients with tracheotomy and mechanical ventilation. Endoscopic evaluation was performed in patients in whom there was respiratory distress with difficulty in passing a suction catheter through the tube, and/or increased inspiratory resistance and increased peak inspiratory pressure. Results: Nineteen patients were diagnosed with granulation or tracheomalacia. Two patients were treated by surgical removal of the obstructing tissue. Nonsurgical patients were conservatively managed with symptoms' resolution by bypassing the pathology with a longer tube than the previous one or by an adjustable flange tube under endoscopic visualization, with a median symptom‐free period of 433 days (range, 55–1230 days). Conclusion: In nonsurgical candidates, insertion of a longer tube is a conservative and feasible long‐term treatment. © 2014 Wiley Periodicals, Inc. Head Neck 37: 716–721, 2015